Interleaved pipeline structures for two-dimensional recursive filtering - Lu, Tongxin, author; Azimi-Sadjadi, Mahmood R., author; IEEE, publisher (Colorado State University. Libraries, 1993)
This paper presents new parallel and pipeline structures for real-time 2-D recursive filtering. For general scalar 2-D recursive filters, a 2-D multiple-interleaved pipeline architecture is introduced that is compatible with the nature of the image-scanning scheme. Using this new structure, the sampling period can be a fraction of the time needed for one scalar addition operation and the delay is only a few samples. In addition, this structure does not need any I / 0 buffers for real-time implementation.
Keywords: pipeline processing; two-dimensional digital filters